2019
DOI: 10.21037/atm.2019.07.63
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance and role of thoracic lymph node metastasis based on Chinese expert consensus in esophageal cancer

Abstract: Background: The Chinese expert consensus on thoracic lymph node (LN) dissection in radical esophagectomy (Chinese Criteria, 2017 edition) was newly promoted. This study examined the prognostic significance and role of thoracic LN metastasis based on the Chinese Criteria for esophageal cancer. Methods: Data of patients with thoracic esophageal squamous cell carcinoma (ESCC) who underwent curative esophagectomy in the West China Hospital from May 2005 to May 2015 were retrospectively analyzed. Patients' prognosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Esophageal cancer (EC) is the seventh most common cancer, and the sixth cancer-related cause of death throughout the world (1). In contrast to adenocarcinoma as the primary histological subtype in Western countries, squamous cell carcinoma accounts for about 90% of EC and ranks as the sixth most common cancer and the fourth leading cause of cancer-related deaths in China (2). Although advances in surgical techniques and therapeutic options during the past decade, ESCC is still characterized by its poor outcome, with a 5-year survival rate of around 25% in China (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Esophageal cancer (EC) is the seventh most common cancer, and the sixth cancer-related cause of death throughout the world (1). In contrast to adenocarcinoma as the primary histological subtype in Western countries, squamous cell carcinoma accounts for about 90% of EC and ranks as the sixth most common cancer and the fourth leading cause of cancer-related deaths in China (2). Although advances in surgical techniques and therapeutic options during the past decade, ESCC is still characterized by its poor outcome, with a 5-year survival rate of around 25% in China (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…An accurate staging system and individualized prognosis prediction could help clinicians to identify patients with poor prognoses 9 correctly; this is essential for ensuring such patients receive a multi-disciplinary treatment regimen to improve the curative effects of treatment on EC. Existing research has identified specific factors that directly influence the occurrence and progress of EC, including the preoperative C-reactive protein/albumin ratio, 10 neutrophil-to-lymphocyte ratio, 11 and thoracic lymph node metastasis, 12 among other factors. [13][14][15][16][17][18] However, currently, there are no methods that can accurately predict postoperative prognosis in patients with stage T1-3N0M0 ESCC.…”
Section: Introductionmentioning
confidence: 99%
“…Lymph node (LN) metastasis has been reported as a signi cant prognostic factor in the patients with thoracic esophageal squamous cell carcinoma (ESCC) [1]. Cancer cells of the thoracic ESCC could spread widely to the cervical and abdominal lymph nodes besides mediastinal lymph nodes through rich longitudinal lymphoid vessels in the submucosa of the esophagus, and this usually leads to poor prognosis [2].…”
Section: Introductionmentioning
confidence: 99%